Nerovnosti v pracovních důchodech - Buchta, Miroslav (Univerzita Pardubice, 2004)
This paper presents and holds forth on reasons of inequality in earned incomes, views on inequality and draws conclusions. It is formulated on the basis of author's experiences and knowledge of literature especially journals.
Keywords: důchodová politika; pracovníci; důchody; diferenciace